Analisis Ijtihad Hukum Membayar Zakat Fitrah dengan Uang Menurut Yusuf Al-Qaradawi dan Wahbah Az-Zuhaili - Matien, Nail Fadhel (Al-Mazaahib: Jurnal Perbandingan Hukum, 2021)
This article defines the difference of ijtihad method used by Yusuf Al-Qaradawi and Wahbah Az-Zuhaili in the legal status of the permission of zakat fitrah payment with money. This article is a qualitative research using data sourced from literature. The data obtained are analyzed using a descriptive-comparative approach. This article shows, that according to Wahbah Az-Zuhaili, based on the jumhur opinion, zakat fitrah must be paid in accordance to the existing text. Meanwhile, Yusuf Al-Qaradawi argues that the payment must be flexible by considering aspects of the benefits that will be received by the poor. Methodologically, Wahbah Az-Zuhaili used qiyās as used in the asy-Syafi'i school. Meanwhile, Yusuf Al-Qaradawi, used the method of Intiqā'i and Insyā'i. This method is used to compare the opinions of scholars, then rated by the aspect of al-muqāranah wa al-muwāzanah. One of the reasons for the determination of staple foods, is, that in ancient times, the use of money as a transaction tool was not popular as it is today. The ever-changing currency value will certainly makes Islamic law (zakat al-fiṭr) not adaptive. However, the value of the benefits of money at this time, can be equated with the benefits of foods in ancient times.